EARLY-LATE ONSET CONDUCT PROBLEMS - Badayai, Abdul Rahman Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Age is always an important criterion in judging behavior, especially towards the development of healthy and deviant behaviors. As such, the age norms would serve as developmental standards, to evaluate the likelihood of young people, especially adolescents, to engage in various conduct problems. Therefore, it is aimed to study age differences (early-late onset) in protective factors, executive dysfunction, and symptoms of problem behaviors and its role in the manifestation of conduct problems in adolescence. Respondents of the study consisted of 404 delinquents of different conduct problems such as armed robbery, drug trafficking, and drug use, gang fights, rape, homicide, and out of control behaviors. Three different instruments were employed in the study, namely, Developmental Assets Questionnaire-Malaysian Version (DAQ-MV), Behavior Rating Inventory of Executive Function- Self Report (BRIEF-SR) and Achenbach System of Empirical Behavior Assessment- Youth Self-Report (ASEBA-YSR). The results based on the one-way ANOVA showed that there were no age differences neither in early nor late onset in the protective factors, executive dysfunction, and symptoms of problem behaviors. Further study and investigation are required in determining an exhibition and consequence of conduct problems either in its early or late-onset. However, the study contributed to the theoretical foundation and psychological ground in developmental psychology and the study of at-risk children and youth.